Prognostic importance of the Controlling Nutritional Status (CONUT) score in patients undergoing cardiac resynchronisation therapy - Yasuo Okumura; Yukitoshi Ikeya; Yuki Saito; Toshiko Nakai; Rikitake Kogawa; Naoto Otsuka; Yuji Wakamatsu; Sayaka Kurokawa; Kimie Ohkubo; Koichi Nagashima (Open Heart)
Aims Malnutrition is common and associated with worse clinical outcomes in patients with heart failure (HF). The Controlling Nutritional Status (CONUT) score is an integrated index for evaluating diverse aspects of the complex mechanism of malnutrition. However, the relationship between the severity of malnutrition assessed by the CONUT score and clinical outcomes of HF patients receiving cardiac resynchronisation therapy (CRT) has not been fully clarified.Methods Clinical records of 263 patients who underwent pacemaker or defibrillator implantation for CRT between March 2003 and October 2020 were retrospectively evaluated. The CONUT score was calculated from laboratory data obtained before CRT device implantation. Patients were divided into three groups: normal nutrition (CONUT scores 0–1, n=58), mild malnutrition (CONUT scores 2–4, n=132) and moderate or severe malnutrition (CONUT scores 5–12, n=73). The primary endpoint was all-cause mortality.Results The moderate or severe malnutrition group had a lower body mass index, more advanced New York Heart Association functional class, higher Clinical Frailty Scale score, lower levels of haemoglobin and higher levels of N-terminal probrain natriuretic peptide (all p<0.05). In the moderate or severe malnutrition group, the CRT response rate was significantly lower than for the other two groups (p=0.001). During a median follow-up period of 31 (10–67) months, 103 (39.1%) patients died. Kaplan-Meier analysis revealed that the moderate or severe malnutrition group had a significantly higher mortality rate (log-rank p<0.001). A higher CONUT score and CONUT score ≥5 remained significantly associated with all-cause mortality after adjusting for previously reported clinically relevant factors and the conventional risk score (VALID-CRT risk score) (all p<0.05).Conclusions A higher CONUT score before CRT device implantation was strongly associated with HF severity, frailty, lower CRT response rate and subsequent long-term all-cause mortality.